2016
DOI: 10.1177/1708538115627718
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of complex aortic aneurysms with fenestrated endografts and chimney stent repair: Systematic review and meta-analysis

Abstract: Objective We reviewed data pertaining to fenestrated endograft technique and chimney stent repair of complex aortic aneurysm for comparative analysis of the outcomes. Methods A comprehensive search of relevant databases was conducted to identify articles in English, related to the treatment of complex aortic aneurysm with fenestrated endovascular aneurysm repair and chimney stent repair, published until January 2015. Results A total of 42 relevant studies and 2264 patients with aortic aneurysm undergoing fenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…2 A recent meta-analysis attempted to compare the vessel patency after treatment of complex aortic aneurysms between fenestrated endografts and chimney stent repair. 3 A total of 2264 patients with complex aortic aneurysms undergoing fenestrated or chimney graft repair were included in this study, analyzing a total of 4413 vessels. The study showed comparative restenosis or occlusion after primary intervention between the 2 techniques (3.6% in fenestrated vs 3.4% in chimney, P = .792).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A recent meta-analysis attempted to compare the vessel patency after treatment of complex aortic aneurysms between fenestrated endografts and chimney stent repair. 3 A total of 2264 patients with complex aortic aneurysms undergoing fenestrated or chimney graft repair were included in this study, analyzing a total of 4413 vessels. The study showed comparative restenosis or occlusion after primary intervention between the 2 techniques (3.6% in fenestrated vs 3.4% in chimney, P = .792).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A recently reported meta-analysis, attempting to compare the outcomes between the 2 techniques regarding the treatment of complex aortic cases, showed that a higher aneurysm-related mortality was observed in chimney stent repair, while fenestrated EVAR was associated with a higher reintervention rate. 3 5…”
Section: Introductionmentioning
confidence: 99%
“…Метаанализ, включивший сведения об имплантации 1884 фенестрированных и 380 параллельных графтов у пациентов с АБА, не пригодной для стандартного эндопротезирования, показал следующие результаты. Общая частота повторных вмешательств в группе фенестрированных графтов составила 11,7%, эндолик IА типа развился в 2% случаев, рестеноз/окклюзия в стентированных ветвях -в 3,6% случаев; в группе параллельных графтов общая частота повторных вмешательств составила 5,6%, эндолик I типа развился в 3,4% случаев, рестеноз/окклюзия в стентированных ветвях -в 3,4% [23].…”
Section: рис 10 коронарограммы больного тunclassified
“…Fenestrated and branched endografts, are endografts with openings and side branches arising directly from the graft and include the visceral artery with the endograft. Recent data suggest that fenestrated and branched endograft placement results in relatively safe, effective, and durable outcomes in highsurgical risk patients treated for complex aortic aneurysms (17,18,44,54,55). As complex EVAR experience and use with branched and fenestrated endografts continue to grow preoperative imaging for endograft customization becomes increasingly important.…”
Section: Complex Evar Optionsmentioning
confidence: 99%